AICCRA report: Capacity Strengthening Workshop for the Rangeland Management Committee, Arbajahan Ward, Wajir West, Wajir County, Kenya - Mukalo, Irene Aloo; Mohamed, Said (International Livestock Research Institute, 2023)
Arbajahan Ward, located within the arid landscape of Wajir West, Wajir County, is home to a resilient pastoral community heavily reliant on rangelands for sustenance. The International Livestock Research Institute (ILRI), in collaboration with the Resource Conflict Institute(RECONCILE), initiated Participatory Rangeland Management (PRM) to build the capacity of local communities to better manage their lands. A Capacity Strengthening Workshop for the Rangeland Management Committee was a pivotal component to this and was successfully held from October 31st to November 2nd, 2023.